Flexible working in organisations : a research overview - Kelliher, Clare, 1962-; Menezes, Lilian M. de (State of the art in business research., 2019)
There is growing interest in flexible working, not only as a means to manage labour more efficiently and for greater agility, but also as a response to increasing concerns over well-being, work-life balance, and participation in the labour force of those with significant non-work commitments (e.g. parents, carers, older workers). As a result, a comprehensive stream of literature on the benefits and challenges of flexible working has developed and led to a body of evidence on the implementation and outcomes of different forms of flexible working arrangements. This book assesses the current state of this literature as follows: Background: the authors review the different definitions that have been proposed, policy developments, availability and uptake. Outcomes from flexible working: the main chapters focus on the outcomes foremployers (e.g. performance, employee retention, organisational commitment etc.), as well as for individual employees (e.g. well-being, job satisfaction etc.). Evaluation of extant knowledge: the authors comment on the existing literature and consider the methodological approaches adopted in the literature. Conclusion: suggestions for future research are proposed. Of interest to students, academics and policy-makers, this book provides an expert overview of the empirical evidence and offers critical commentary on the state of knowledge in the field of flexible working and new forms of work.